2020
DOI: 10.1111/are.14782
|View full text |Cite
|
Sign up to set email alerts
|

Polyculture of White shrimp (Penaeus vannamei) and sea cucumber (Holothuria inornata) in a biofloc system

Abstract: In order to improve the cost-benefit relationship in aquaculture production systems, several technological advances have been formulated. The biofloc technology system (BFT) offers the advantage of functioning as a water treatment method, allowing the conversion of ammonium to nitrites and nitrates by using the properties of chemo-autotrophic bacteria. Biofloc technology system is considered a relevant cost-effective and ecological method, with potential use in aquaculture (Crab, Defoirdt, Bossier, & Verstraet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Sustainable integrated or polyculture of milk fish, shrimps and seaweed: The future is in sustainable intensification of polyculture, for example by co-culturing milkfish, shrimps, holothurians and seaweed ( Contreras-Sillero et al . 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sustainable integrated or polyculture of milk fish, shrimps and seaweed: The future is in sustainable intensification of polyculture, for example by co-culturing milkfish, shrimps, holothurians and seaweed ( Contreras-Sillero et al . 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ge et al (2019) demonstrated that the integration of L. vannamei (500 shrimp m -3 ) and green seaweed Ulva prolifera (800 mg L -1 ) with 10% water exchange improve the water quality and enhance shrimp growth. Contreras-Sillero et al (2020) showed that polyculture of L. vannamei and sea cucumber Holothuria inornata in a BFT based recirculation system was feasible, and this system provide the excellent growth, survival and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Polyculture of shrimp with sea cucumber ( Holothuria inornata ) in a biofloc system also revealed a satisfactory yield without influencing the survival of H . inornata (Contreras‐Sillero et al, 2020). The giant freshwater prawn Macrobrachium rosenbergii is an excellent candidate for polyculture systems.…”
Section: Introductionmentioning
confidence: 99%